Pour Jean Laude. (Saint-Etienne : Musée d'Art Moderne, 1991)
Bazaine, Jean ; Bonniel, Pierre ; Braque, Georges ; Bucaille, Max ; Byzantios, Constantin ; Cardenas, Augustin ; Chavignier, Louis ; Collinet-Baillon, Marie-Hélène ; Cremonini, Leonardo ; Domela, Cesar ; Ernst, Max ; Fourniau, Catherine ; Frolet, Elisabeth ; Giacometti, Alberto ; Girardin, Hervé ; Hartung, Hans ; Jacobsen, Robert ; Klee, Paul ; Lam, Wifredo ; Lancri, Jean ; Lardera, Berto ; Laurens, Henri ; etc.
Pour Jean Laude, Musée d'Art Moderne, Saint-Etienne, 15.11 - 23.12.1991 ; Chapelle de la Sorbonne, Paris, 1992
boek